Building condition assessment : PWD Quarters Jalan Bruseh / Muhammad Irfan Hakimi Wira - Wira, Muhammad Irfan Hakimi (Universiti Teknologi Mara, Perak, 2016)
Basically, building is anything that is built with walls and roof that is used as a place for people to live, work, do activities and store things. Buildings are categorized in term of their architectural functions. It can be divided into five main categories which are residential buildings, commercial buildings, educational building, industrial buildings, government buildings and agricultural buildings. A building defect is defined as a material, component or finish which does not meet its expected performance criteria.